Production of Squalene in Bacillus subtilis by Squalene Synthase Screening and Metabolic Engineering - Song, Yafeng (J Agric Food Chem, 2020)
[Image: see text] Squalene synthase (SQS) catalyzes the conversion of two farnesyl pyrophosphates to squalene, an important intermediate in between isoprene and valuable triterpenoids. In this study, we have constructed a novel biosynthesis pathway for squalene in Bacillus subtilis and performed metabolic engineering aiming at facilitating further exploitation and production of squalene-derived triterpenoids. Therefore, systematic studies and analysis were performed including selection of multiple SQS candidates from various organisms, comparison of expression vectors, optimization of cultivation temperatures, and examination of rate-limiting factors within the synthetic pathway. We were, for the first time, able to obtain squalene synthesis in B. subtilis. Furthermore, we achieved a 29-fold increase of squalene yield (0.26–7.5 mg/L) by expressing SQS from Bacillus megaterium and eliminating bottlenecks within the upstream methylerythritol-phosphate pathway. Moreover, our findings showed that also ispA could positively affect the production of squalene.